PERUBAHAN FISIKOKIMIA FULL FAT MAYONNAISE DENGAN PENAMBAHAN SARI JAHE SEBAGAI ANTIOKSIDAN ALAMI SELAMA PENYIMPANAN: PHYSICOCHEMICAL CHANGES OF FULL FAT MAYONNAISE WITH THE ADDITION OF GINGER EXTRACT AS A NATURAL ANTIOXIDANT DURING STORAGE - Safitri, Alief Rahmania; Sari, Dewiarum; Ali, Muhammad Irvan; Atmaja, Baluh Medyabrata; Hutabarat, Amelia Lulu Rosalin; Lestari, Wenni Meika; Ali, Abdul Muta; Hidayatulloh, Rifqi (Universitas Boyolali, 2025)
Mayonnaise is an oil-in-water emulsion product that is highly susceptible to degradation during storage, including phase separation, lipid oxidation, and discoloration. The objective of this study was to evaluate the impact of incorporating three different types of ginger extracts (red ginger, elephant ginger, and emprit ginger) at a concentration of 1.5% on the physicochemical stability of full-fat mayonnaise over a month storage period. Parameters assessed included emulsion stability, color attributes (L, a, b*), moisture content, fat content, and pH on days 0, 7, 14, 21, and 28. The study employed a nested Completely Randomized Design (CRD), and data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test. The results indicated that the addition of red ginger extract significantly improved emulsion stability, preserved color brightness, slowed the increase in moisture content, and mitigated the decline in fat content during storage. The addition of ginger extract exhibited no significant effect on pH variations. The antioxidant and antimicrobial activities of bioactive compounds in red ginger were instrumental in maintaining the quality of mayonnaise throughout storage. These findings highlight the potential of red ginger extract as a natural additive to enhance the physicochemical stability of full-fat mayonnaise for up to 21 days under ambient storage conditions.